2020
DOI: 10.46662/jass-vol7-iss1-2020(21-27)
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Life Satisfaction of Teachers Working at Special Education Institutions of Bahawalpur, Pakistan

Abstract: The present study compared the level of life satisfaction and emotional intelligence of teachers employed at special education institutes, and teachers working at regular education institutes. The purposive sampling was used to select the sample for this study. The sample of the study was comprised of 100 teachers, 50 (male=25, female=25) working at special education institutions and 50 (male=25, female=25) regular education institutions of Bahawalpur, Pakistan. The age range of participants was 21-60 years. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
2
1
1
Order By: Relevance
“…The current study does not show significant gender differences in terms of presence of meaning in life and life satisfaction. Previously it has been shown that female teachers used to have high level of meaning in life (Bektas, 2012) but in terms of non-significant gender differences in life satisfaction, findings are consistent with a previous study conducted by Anjum et al (2020) and Deniz et al (2010). Because both male and female teachers have the same tasks and activities to perform at their workplace and they might also have equal opportunities to grow professionally that makes insignificant gender difference in terms of life satisfaction (Tin & Tun, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current study does not show significant gender differences in terms of presence of meaning in life and life satisfaction. Previously it has been shown that female teachers used to have high level of meaning in life (Bektas, 2012) but in terms of non-significant gender differences in life satisfaction, findings are consistent with a previous study conducted by Anjum et al (2020) and Deniz et al (2010). Because both male and female teachers have the same tasks and activities to perform at their workplace and they might also have equal opportunities to grow professionally that makes insignificant gender difference in terms of life satisfaction (Tin & Tun, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Current findings are consistent with previous study conducted by Kumar (2014) who found that there was non-significant difference regarding life satisfaction referring to the type of educational institutions. There also have been observed some contrary results in literature where teachers from special education systems used to have high life satisfaction (Anjum et al, 2020) and opposite to it special education teachers tend to be more dissatisfied than other teachers (Girgin & Baysal, 2002) but in present study, life satisfaction seems independent of educational settings.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations